Analisis Yuridis terhadap Keabsahan Sertifikat Tanah yang Diterbitkan secara Tumpang Tindih (Studi Putusan Mahkamah Agung Nomor 392 K/TUN/2022) - Yehezkiel Ludwyg Milala; Hasim Purba; Suprayitno (CV Rewang Rencang, 2025)
Idonesia's land registration system, which applies a negative publication system with positive tendencies, has led to frequent occurrences of overlapping land certificates due to weaknesses in the verification of physical and juridical data, lack of system integration, and insufficient administrative accuracy. The research method employed is a normative juridical approach. The legal consequences of such disputes include legal uncertainty, annulment of certificates issued later due to administrative defects, reinforcement of the legal standing of certificates issued earlier based on the principle of prior in tempore potior in jure, as well as the legal liability of the National Land Agency, including the obligation to revoke defective certificates and to provide legal protection to good-faith purchasers. Supreme Court Decision Number 392 K/TUN/2022 affirms the annulment of defective certificates and emphasizes the importance of the principle of prudence as the foundation for the issuance of land certificates.